INVESTIGATION OF SELF EFFICACY IN THERAPY MANAGEMENT IN TYPE 2 DIABETES MELLITUS PATIENTS THE COVID-19 PANDEMIC. - Robiul Fitri Masithoh; Margono Margono (Jurnal Keperawatan BSI, 2021)
Self-efficacy is a belief that a person can successfully carry out the expected behavior to get certain results and the beliefs and expectations of each individual are different, because behavior can be carried out if the individual believes that practice or action produces different results. Especially with the condition of the Corona virus outbreak causing a lot of concern in the community, especially those with comorbid diseases, including diabetes which can worsen the condition of a person infected with Covid. So that to suppress the worsening of conditions for controlling blood sugar levels, it is necessary to investigate self-efficacy in the management of therapy in patients with Diabetes Mellitus. Objective To determine self-efficacy in the management of therapy in patients with Diabetes Mellitus during the Covid 19 pandemic. To achieve this goal, it is carried out through a descriptive correlation method with a cross sectional approach with measurement and observation; conducting library studies, surveys, and compiling and developing instruments in the form of questionnaires as well as data collection and problem identification. The results of this study are the average value of self-efficacy is 1.4 with a capable category and the average value of education is 1.7 with a good category. The results of the analysis using personal correlation show a significant relationship between self-efficacy and education in therapy management (p value = 0.000 during the covid 19 pandemic. Conclusion: there is a significant relationship between self-efficacy and education in type 2 diabetes mellitus patients at the North Magelang Health Center